Chirripó Hydrological Research Site: advancing stable isotope hydrology in the Central American Páramo - Esquivel-Hernandez, Germain (2020)
The Chirripó Hydrological Research Site (CHRS) is located within the Chirripó National Park, Costa Rica (between 3,100-3,820 m asl) whereby ~100 km2 are covered by Páramo, a high‐elevation tropical grassland ecosystem. A lake district with approximately 30 lakes of glacial origin is also protected in this area. The CHRS has been monitored since April 2015 with the aim of establishing the first water isotope baseline for the Central American Páramo. At a regional scale, the water isotope ratios (δ2H and δ18O) in precipitation and surface water at CHRS are useful to describe the governing moisture transport from the Caribbean Sea and Pacific Ocean and the complex rainfall producing systems across the N-S mountain range of Central America. These data are also providing unique information about the evaporation and water balance conditions of tropical glacial lakes and the formation of orographic and convective precipitation in high‐elevation tropical ecosystems. Current data sets from CHRS include continuous lake water temperature and meteorological conditions (i.e., precipitation amount, air temperature and relative humidity), as well as water stable isotopes in precipitation, stream water, and lake water (daily to biweekly sampling frequency). Stream water is collected at several locations across the topographic gradient whereas lake water is sampled in the three main lake systems of CHRS. CHRS serves as a reference site for conducting pilot isotopic research in high-elevation ecosystems to advance the atmospheric, hydrogeological and ecohydrological studies in these understudied biomes. All data from April 2015 to November 2020 are publicly available